Uma análise retórica do gênero defesa pública - Melo, Deywid Wagner de (2008)
This work has the objective to do rhetoric analysis in the genre public defense in the spoken language. It intends to show linguistic mechanisms that people, lawyers and promoters, use in defense of their arguments. We understand Rhetoric as the art of persuading in discourse. The theoretical basis of our investigation concerns Rhetoric is in Perelman and Olbrechts-Tyteca (2005), Reboul (2004) and Abreu (2004), refences to conversation analysis in Marcuschi (1998, 2003) and concerns to text linguistics in Koch (1984, 1992, 2003, 2005) and Santos (1999, 2002). The focus of analysis is the judicial scenery, exactly the jury session, where the rhetoric spoken the lawyer, is in the Defense and the promoter is in the accusation of the Public Ministry deliver their text/discourse intending to adhere the auditorium: it is a popular jury. The analysis showed that rhetoric moments objected the adhesion to who the thesis of defense is presented. It is mean, the construction of the sense to persuade the auditorium of the chosen place really happened.